Children's Education According to Abdullah Nashih Ulwan: Forming A Person with Noble Character in The Context Of Islam - Najamudin, Najamudin (Raudhah Publisher, 2024)
Education is a learning process that aims to develop individual potential and abilities in order to achieve physical, intellectual, emotional, and social maturity. Education involves the transfer of knowledge, skills, values, and attitudes to the younger generation or individuals in society. Education is a cultural process so that human dignity can be increased, which of course must be based on Islamic education as the main foundation for quality improvement. The awareness that educating children is the responsibility of parents as the main task, according to Abdullah Nashih Ulwan, the process of educating children is not limited to a verbal context, but involves all aspects of life universally. This study aims to analyze the concepts of children's education according to Abdullah Nashih Ulwan and how these concepts can be used to form a person with noble character in the context of Islam. This study uses a descriptive-analytical method with a qualitative approach. Data were obtained through literature studies involving the works of Abdullah Nashih Ulwan and other related sources. The concepts of children's education according to Abdullah Nashih Ulwan which are analyzed by producing several conclusions include the formation of noble morals, the development of religious knowledge, character education in Islam, and the role of the family in children's education. The results of the study show that Abdullah Nashih Ulwan's concepts have high relevance in shaping a person with noble character in children. The formation of noble morals involves teaching Islamic values, habituation, and consistent direction. The development of religious knowledge is important to strengthen children's spiritual foundation. Character education in Islam emphasizes the development of noble qualities such as honesty, a sense of responsibility, and tolerance. In addition, the strong role of the family in children's education is an important factor in the implementation of these concepts.